Investigation of the Installation Environmental Impact to the Calculated Life Expectancy of Bearings - Makris Nikolaos; Siasos Alexandros (2017)
Abstract, Acknowledgements, Introduction, Background, Aims and Objectives, Literature Review, Basic Theory, Bearing Failure, Predictive Bearing Maintenance, State of the Art, Important Parameters Concerning Bearings' Function, Methodology of Test Rig Construction Techniques, Environmental Conditions During Assembly, Methoda of Measurement, Findings of the Test Rig Experiment, Critical Analysis Report, Study Limitations, Future Research, Conclusions, References, Appendices.